Exploring tannin structures to enhance enzymatic polymerization - Romero, Romina; Gonzalez, Tihare; Urbano, Bruno F.; Segura, Cristina; Pellis, Alessandro; Vera, Myleidi (Frontiers in Chemistry, 2025)
The enzymatic polymerization of biomass-derived polyphenols presents a sustainable approach to producing advanced materials. However, the structural diversity and incomplete characterization of tannins pose challenges to optimizing the process. This study investigates how tannin composition and the presence of phenolic and non-phenolic compounds in aqueous Pinus radiata bark extracts influence laccase-catalyzed polymerization and the resulting material’s thermal and structural properties. The extracts were characterized using proximate and ultimate analysis, Py-GC/MS, FT-IR, TGA, and phenol content analysis before polymerization with Myceliophthora thermophila laccase (MtL). Structural and thermal analysis of the polymers revealed significant transformations driven by enzymatic oxidation. Tannin extracts rich in resorcinol and low in carbohydrates and less polar compounds produced highly cross-linked polymers with exceptional thermal stability, retaining 86% residual mass at 550°C. These findings demonstrate that tannin composition plays a key role in polymerization efficiency and material performance. The resulting thermally stable polymers offer potential applications in flame retardancy and sustainable material development, providing a promising pathway for biomass valorization.